Role Of biodiversity: Importance of food for the development of Peru - Mostacero León, José (2017)
Perú is considered a Megadiverse Country, because it has: 70% of the planet's biodiversity. It is estimated that it has 25,000 species of plants (10% of the world total), where we have the first place in potato varieties (3000 var.), Corn (55 breeds), tomato (15 wild species and 2 domesticated), peppers, Andean grains (quinoa, kiwicha, cañigua), tropical fruits, etc .; likewise a varied geography, soil science, geology, ecology, which in turn determines a broad biogeographical division, many ecological zones, great diversity of habitats, rich diversity of plants and animals with a high percentage of endemic flora and fauna; distributed with 8 Natural Regions: Costa or Chala, Yunga, Quechua, Suni or Jalca, Puna, Janca or Cordillera, Rupa Rupa or Selva Alta and Omagua or Selva Baja, with 84 of the 117 LIFE ZONES of the world (71.8% of the total world).We must also consider that 40% of the world's food has been domesticated in Peru, becoming the largest Genetic Center in the world.